A longitudinal twin study on Tojikomori and depressive symptoms in Japanese elderly. Issue 4 (29th September 2015) - Inui, Fujio; Honda, Chika; Kato, Kenji; Tomizawa, Rie; Nishihara, Reiko; Hayakawa, Kazuo
Abstract: Background: Genetic factors associated with Tojikomori (being housebound without any limitations in physical functioning or mental problems) are unclear. We performed a twin study to help clarify the causes of Tojikomori and investigate the association between Tojikomori and depressive symptoms. Methods: Participants were members of the Osaka University Aged Twin Registry. A total of 157 twin pairs (314 individuals) who provided data in 2008 and 2012 were included. Depressive symptoms were measured by the Geriatric Depression Scale short version (GDS). Social Activities Scores (SAS) were measured with questions assessing the frequency of going out and contact with others. Activities of daily living were assessed with the Barthel index. Structural equation modelling analysis was used to evaluate the relative importance of genes and environments for the phenotypes measured. Results: In the first analysis, for SAS (2012), 25% of the variance was explained by additive genetic effects, and 75% was explained by unique environmental (including error) effects. For the GDS (2012), 28% of the variance was explained by additive genetic effects, and 72% was explained by unique environmental (including error) effects. In the second analysis, 25% of the total variance in SAS (2012) was explained by additive genetic factors, which influenced GDS scores (2008 and 2012). However, only 10% of the total variance in GDS scores (2012) was explained by additive genetic factors that influenced SAS (2008 and 2012). Conclusions: Tojikomori was influenced by genetic factors in the elderly Japanese subjects. The association between Tojikomori and depressive symptoms was explained by genetic and environmental factors that are common to both phenotypes. Depressive symptoms were a cause of future Tojikomori and were affected by additive genetic factors. Genetic factors of Tojikomori were not a major cause of future depressive symptoms.